Análisis Del Efecto De La Adición De Fibra Cítrica Del Bagazo De La Naranja En Las Propiedades Nutrimentales Y Sensoriales De Un Embutido Y Determinación De La Calidad Microbiológica - Temani Durán-Mendoza; Manuel González-Pérez; María Concepción de la Cruz-Leyva; José Ulises González-de la Cruz; Carlos Alberto Cuenca-Soria; Juan Guzmán-Ceferino; Jesús Ofelia Angulo-Guerrero; Carolina del Carmen Pérez-Sánchez (European Scientific Journal, ESJ, 2018)
The orange bagasse (Citrus sinensis) is a residue with a significant content of citrus fiber (FC); it is used as a functional ingredient in the development of new products. We consider it essential to know the effect of the nutritional and sensorial properties of FC. The objective of this research was to evaluate the effect of powdered the orange bagasse on the nutritional and sensorial properties of pork and beef sausage. The sausage was prepared by mixing the proportions of minced pork and beef with the corresponding FC, adding spices, orange juice and a solution of natural dye Bixa Orellana, after 24 hours of maturation was stuffed into cellulose casings. A randomized design with three repetitions was used. The treatments were formulations with 0, 5, 10 and 15% of FC respectively, named treatments E0, E5, E10 and E15. The chemical variables evaluated were: moisture content, ash, fat, protein (analyzed by the AOAC method, 1990), and total dietary fiber (by the methodology described by Asp et al., 1983 and Prosky et al, 1988); the microbiological variables: aerobic mesophiles, total and fecal coliforms, Salmonella and Staphylococcus aureus, detected and quantified with the methods of the corresponding Official Mexican Standards. The sensory variable was the level of liking which was evaluated in 128 consumers, and a commercial sausage called "EC" was used. As a comparison product. In E5, E10 and E15 the fat levels decreased (p <0.05). The ash increased as a function of the addition of FC. Regarding protein, no differences were observed between E0 and E5. In the treatments, E10 and E 15 the protein decreased significantly. Total dietary fiber at E5, E10, and E15 ranged from 4.38 to 10.50%. The consumer test favored E0, E5, and EC. We conclude that the orange bagasse exerts a positive effect by decreasing fat and increasing total dietary fiber. Aleson-Carbonell et al. (2003) report similar behavior. It is concluded that it is feasible to add FC no higher than 5% as an alternative to enrich sausages.